2022
DOI: 10.1002/admi.202200808
|View full text |Cite
|
Sign up to set email alerts
|

Pt Single Atoms on TiO2 Polymorphs—Minimum Loading with a Maximized Photocatalytic Efficiency

Abstract: For more than 20 years, Pt/TiO2 represents the benchmark photocatalyst/co‐catalyst platform for photocatalytic hydrogen (H2) generation. Here, single atom (SA) Pt is decorated on different polymorphs of TiO2 (anatase, rutile, and the mixed phase of P25) using a simple immersion anchoring approach. On P25 and anatase, Pt SAs act as highly effective co‐catalyst for pure water splitting with a photocatalytic H2 evolution activity (4600 µmol h−1 g−1)—on both polymorphs, SA deposition yields a significantly more ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 59 publications
(112 reference statements)
2
42
0
Order By: Relevance
“…On both types of sputtered layers, SA Pt deposition was carried out from a H 2 PtCl 6 solution at three different concentrations (0.005 mM, 0.05 mM, and 2 mM) using a deposition process described previously. 15,17,28 Figure 1a−c shows HAADF-STEM images for deposition from differently concentrated Pt precursor solutions. For all precursor concentrations, Pt SA decoration is apparent on the anatase TiO 2 surface (the lattice spacing of 0.354 nm corresponds to the (101) plane of anatase).…”
mentioning
confidence: 99%
“…On both types of sputtered layers, SA Pt deposition was carried out from a H 2 PtCl 6 solution at three different concentrations (0.005 mM, 0.05 mM, and 2 mM) using a deposition process described previously. 15,17,28 Figure 1a−c shows HAADF-STEM images for deposition from differently concentrated Pt precursor solutions. For all precursor concentrations, Pt SA decoration is apparent on the anatase TiO 2 surface (the lattice spacing of 0.354 nm corresponds to the (101) plane of anatase).…”
mentioning
confidence: 99%
“…The Pt SAs on the Co 3 O 4 have shown a higher valence state of ~4+ and a larger population of unoccupied Pt 5d states [90]. Similar investigations were also performed to investigate the Pt 5d occupation state of Pt SA compared to small clusters or nanoparticles (on graphene) [91], for Pt SAs on FeOx [92] or on different polymorphs of TiO 2 nanoparticles [93] and for bi-metallic SAs of PtAu [94].…”
Section: X-ray Absorption Near Edge Structure (Xanes) and Extended X-...mentioning
confidence: 98%
“…Recently Wei et al [94] reported on the synthesis of bi-metallic single-atoms on different facetted TiO2 ({001},{101}), where the metal-support interactions that originated from the coordinatively unsaturated sites contributed to the anchoring of the atomic cocatalysts-namely, onto {001}-TiO2 through Pt-O and Au-O bonds, while on {101}-TiO2 Similarly, the coordination of Pt SAs on different supports (TiO 2 [93]) or of other SAs (Au on TiO 2 [82]) can also be evaluated. For example Wan et al [82] reported on the isolated single atomic dispersion of Au on defective TiO 2 , with an Au-O shell (R = 1.6 Å) and an Au-Ti shell (R = 2.4 Å), without Au-Au and Au-Cl coordination peaks (compared with Au foil and HAuCl 4 as reference).…”
Section: X-ray Photoelectron Spectroscopy (Xps) For Sa Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major challenges to address is that Pt SAs without strong binding sites can be thermodynamically unstable due to their high surface energies and hence tendencies to agglomerate during multiple reaction cycles. For these reasons, a high surface area support with sufficient strong coordination sites is necessary to firmly anchor Pt SAs onto the TiO 2 matrix. …”
Section: Introductionmentioning
confidence: 99%